Fostering Higher Order Thinking in English as a Foreign Language Learners: Teachers' Reflections and Practices and Students' Readiness Case of Third Year LMD Students of English at Mohamed Cherif Messaadia University, Souk Ahras - Hibatallah AOUADI (My University, 2023)
Abstract Teachers’ practices together with the teaching techniques they make use of should be implemented to foster the different factors that can make effective learning take place. One of these factors is promoting higher-order thinking(HOT) in learners. Therefore, the current study aims to find out whether EFL teachers at Mohamed CherifMessaadia University find it necessary to foster higher order thinking skills(HOTS), including the levels of analysis, evaluation, and creativity which were suggested in the revisited version of Bloom’s Taxonomy. It also attempts to explore students’ readiness to develop HOTS. To achieve the research goals, and to answer our research questions, an exploratory research was conducted through the use of an interview with four teachers, a questionnaire with 94 third year students in addition to classroom observation of five sessions at the department of English at Mohammed CherifMessaadia University, Souk-Ahras. The findings revealed that the majority of students are not ready enough to develop HOT. They are interested in memorizing and understanding rather that analysing or criticising information. Besides, the sense of analyzing and evaluating is ignored by the third-year EFL students and enhancing students’ creativity is considered as a difficult if not impossible task for some teachers. ----------------- الملخص يحتاج الأساتذة إلى عدد متزايد من الاستراتيجيات لتحقيق نجاح الطلاب وضمان فهمهم. واحدة من أكثر الاستراتيجيات فعالية هي التفكير عالي النظام. يستخدم أساتذة اللغة الإنجليزية كلغة أجنبية ثلاث استراتيجيات من تصنيف بلوم لتطوير التفكير النقدي للطلاب وقدراتهم المعرفية. تصنيف بلوم هو أفضل طريقة لتقييم مستوى الفهم باستخدام مستويات مختلفة من التفكير عالي النظام ، وهي (تحليل وتقييم وإنشاء). التفكير العالي هو استراتيجية مفيدة للطلاب لتطوير قدراتهم المعرفية ، ويساعد في تحسين صنع القرارات وحل المشكلات وتعزيز الإبداع. يعزز التفكير العالي فهمًا أعمق للمعلومات المستحوذة بدلاً من مجرد حفظها على مستوى السطح. يعتبر مستوى التحليل و تقييم و الابداع منسي تمام في جامعة محمد شريف مساعدية بالتحديد قسم اللغة الانجليزية كم يعتبر تطوير حس الابداع لدى طلبة السنة الثالثة انجليزية صعب بالنسبة للأساتذة --------------------- Résumé Les enseignants ont besoin d’un nombre croissant de stratégies pour atteindre le succès des élèves et assurer leur compréhension. L’une des stratégies les plus efficaces est ( higherorderthinking ) pensée d'ordre supérieur. Les enseignants de l'EFL utilisent trois stratégies de la taxonomie de Bloom pour développer la pensée critique des élèves et leurs capacités cognitives. La taxonomie de Blooms est la meilleure façon d'évaluer le niveau de compréhension en utilisant différents niveaux de pensée d'ordre supérieur ( higherorderthinking) à savoir : (Analyser, évaluer, créer)La pensée d'ordre supérieur est une stratégie bénéfique pour les étudiants de développer leurs capacités cognitives et il aide à améliorer la prise de décision et la résolution de problèmes ainsi que l'amélioration de la créativité. La pensée d'ordre supérieur favorise également une compréhension plus profonde de l'information retenue plutôt que de la simple mémorisation au niveau de la surface. Les méthodes et les stratégies du professeur dépendent du niveau et de l'intérêt des élèves. Dans l'université MCM spécifiquement le département de l'anglais dans les classe de troisième année EFL la majorité des étudiants sont intéressés à mémoriser l'information plus que la compréhension, le sens de L'analyse et l'évaluation sont ignorées par les étudiants de la troisième année de l'EFL.Les enseignants rêvent de la créativité de l'élève, l'amélioration de la créativité des élèves est un peu difficile pour certains professeurs